Il vento, respiro del cielo e della terra - Crosina, Maria Luisa (Annali di studi religiosi, 2004)
This essay deals with wind as a physical entity and intends to show how spatially and temporarily distant cultures have mad it the object – ascribing the same characteristics and properties to it – of analogue myths and beliefs.